The development of biodegradable plastic from hemp by microbial stimulus - Moscoso-Gama, Johanna Marcela (2024)
Currently, several industries have opted for the use of Cannabis sativa for different purposes, this time the capacity of the hemp stem fiber in conjunction with the Ralstonia eutropha bacterium for innovation of biodegradable plastics is highlighted, taking advantage of its potential for the generation of PHB (Polyhydroxybutyrate). This review article supports the analysis of sources such as scientific articles and research papers related to the artisanal and industrial manipulation of hemp fibers, as well as previous research regarding the production of PHA by the bacteria. The perspective is to develop a methodology with easily accessible resources in Colombia. The results show that the investigations carried out recently and the raw material is a good factor in economy, management, and progress; Additionally, different studies show that cassava is recognized as a great source of carbon that increases the potential for PHB production by the bacteria. It is concluded that its composting does not require third parties. Still, only the environment because of the power that Ralstonia eutropha has to produce PHB and that under conditions of physiological stress, it is capable of degrading, allowing to reduce the impact of the degradation of the material in the environment without contamination or residual microplastics.